AP2/ERF Transcription Factor NbERF-IX-33 Is Involved in the Regulation of Phytoalexin Production for the Resistance of Nicotiana benthamiana to Phytophthora infestans - Imano, Sayaka; Fushimi, Mayuka; Camagna, Maurizio; Tsuyama-Koike, Akiko; Mori, Hitoshi; Ashida, Akira; Tanaka, Aiko; Sato, Ikuo; Chiba, Sotaro; Kawakita, Kazuhito; Ojika, Makoto; Takemoto, Daigo (Frontiers in Plant Science, 2022)
Plants recognize molecular patterns unique to a certain group of microbes to induce effective resistance mechanisms. Elicitins are secretory proteins produced by plant pathogenic oomycete genera including Phytophthora and Pythium. Treatment of INF1 (an elicitin produced by P. infestans) induces a series of defense responses in Nicotiana species, including reactive oxygen species (ROS) production, hypersensitive cell death and accumulation of the sesquiterpenoid phytoalexin capsidiol. In this study, we analyzed the expression profiles of N. benthamiana genes after INF1 treatment by RNAseq analysis. Based on their expression patterns, N. benthamiana genes were categorized into 20 clusters and 4,761 (8.3%) out of 57,140 genes were assigned to the clusters for INF1-induced genes. All genes encoding enzymes dedicated to capsidiol production, 5-epi-aristolochene (EA) synthase (NbEAS, 10 copies) and EA dehydrogenase (NbEAH, 6 copies) and some genes for ethylene production, such as 1-aminocyclopropane 1-carboxylate (ACC) synthase (NbACS) and ACC oxidase (NbACO), were significantly upregulated by INF1 treatment. Analysis of NbEAS1 and NbEAS4 promoters revealed that AGACGCC (GCC box-like motif) is the essential cis-element required for INF1-induced expression of NbEAS genes. Given that the GCC box is known to be targeted by ERF (ethylene-responsive factor) transcription factors, we created a complete list of N. benthamiana genes encoding AP2/ERF family transcription factors, and identified 45 out of 337 AP2/ERF genes in the clusters for INF1-induced genes. Among INF1-induced NbERF genes, silencing of NbERF-IX-33 compromised resistance against P. infestans and INF1-induced production of capsidiol. Recombinant NbERF-IX-33 protein can bind to the promoter sequence of NbEAS4, suggesting that NbERF-IX-33 is a transcription factor directly regulating the expression of genes for phytoalexin production.